The Role of Ecopreneurship on Women's Empowerment in Surabaya - Wininatin Khamimah; Dewi Urip Wahyuni; Eka Yuliati (Jurnal Ekonomi Manajemen Bisnis dan Akuntansi, 2026)
Ecopreneurship embodies the capacity to identify everyday community challenges and transform them into viable business opportunities that simultaneously address environmental issues. The spirit of ecopreneurship aligns with efforts to empower women, particularly housewives. Those who previously lacked independent income now gain greater empowerment through ecopreneurship. This study aims to: 1) Analyze the role of ecopreneurship in enhancing women's economic and social independence in Surabaya; 2) Formulate ecopreneurship as a policy recommendation for the Surabaya City Government in green economy-based empowerment programs. This research adopts a qualitative approach, with the primary method being a literature review, without requiring primary data collection in the field. All data sources are secondary, encompassing various materials related to the research object, such as academic textbooks, peer-reviewed scientific journals, national and international seminar papers, official government reports, and other credible publications. This study finds that in the Surabaya context, ecopreneurship is highly relevant for women through the utilization of local potentials, such as organic waste processing or upcycled products, to support the city's green economy. Ecopreneurship proves effective in enhancing women's economic and social independence in Surabaya. Ecopreneurship can also serve as a policy recommendation for the Surabaya City Government in green economy-based empowerment programs.